Effectivity of karamunting Melastoma malabathricum leaves in inhibiting ovarian development of Nile tilapia Oreochromis niloticus - Yogo Tri saloko; Muhammad Agus Suprayudi; Muhammad Zairin Jr. (Indonesian Society of Scientific Aquaculture (ISSA), 2022)
ABSTRACT Tilapia gonads mature quickly before reaching market size, caused by a diverting of feed energy from growth to reproduction. As a result, somatic growth is disrupted to achieve market size, the operational costs are high, and the rearing period is longer. This study aims to evaluate the ability of karamunting leaf extracts to inhibit the development of tilapia gonads. This study used a complete randomized design with four treatments and three replications, namely 0 mg/kg, 25 mg/kg, 50 mg/kg, and 100 mg/kg of karamunting leaf extract. Tilapia fish weighed 13–14 g were kept in an aquarium measuring 100×60×50 cm with a stocking density of 20 fish/ aquarium. Fish were fed twice a day at 8 a.m and 5 p.m in at satiation. Sampling was carried out at the beginning of the study, on day 30th and day 60th. On day 30th the result showed that the best dose in inhibiting the development of fish gonad was 100 mg/kg of karamunting leaf extract that was 1.15 ± 0.19% and the daily growth rate was increased at 2.22 ± 0.06%. On day 60th, the best dose in inhibiting gonad development was 25 mg/kg of karamunting leaf extract, which was 2.49 ± 1.24% and the daily growth rate was increased amount 3.26 ± 0.06%. Keywords: extract, karamunting leaves, gonad development, tilapia ABSTRAK Gonad ikan nila cepat berkembang sebelum mencapai ukuran pasar, menyebabkan pengalihan energi pakan dari pertumbuhan ke reproduksi. Akibatnya, pertumbuhan somatik terganggu sehingga untuk mencapai ukuran pasar biaya operasional tinggi dan masa pemeliharaan lebih lama. Penelitian ini bertujuan untuk mengevaluasi ekstrak daun karamunting dalam menghambat perkembangan gonad ikan nila. Penelitian ini menggunakan rancangan acak lengkap dengan empat perlakuan dan tiga ulangan; yaitu 0 mg/kg, 25 mg/kg, 50 mg/kg, dan 100 mg/kg ekstrak daun karamunting. Ikan nila berukuran 13–14 g dipelihara di akuarium berukuran 100×60×50 cm dengan padat tebar 20 ikan/akuarium. Ikan diberi makan dua kali sehari pada jam 8 pagi dan 5 sore dengan at satiation. Pengambilan sampel dilakukan pada awal penelitian, hari ke-30 dan hari ke-60. Hasil pada hari ke-30 menunjukan bahwa dosis terbaik dalam menghambat perkembangan gonad pada ikan uji adalah 100 mg/kg ekstrak daun karamunting yaitu 1.15 ± 0.19% dan meningkatkan pertumbuhan harian 2.22 ± 0.06%. Pada hari ke-60 dosis terbaik dalam menghambat perkembangan gonad adalah 25 mg/kg ekstrak daun karamunting yaitu 2.49 ± 1.24% dan meningkatkan pertumbuhan harian 3.26 ± 0.06%. Kata kunci: daun karamunting, ekstrak, ikan nila, pertumbuhan gonad